A tetravalent live attenuated dengue virus vaccine stimulates balanced immunity to multiple serotypes in humans - Usha K. Nivarthi (Nature Portfolio, 2021)
Multivalent vaccines that confer protection to multiple serotypes of Dengue virus have been established. Here the authors examine the presence of vaccine induced multivalent antibodies and how these link to protection in a human challenge model of Dengue virus.